2018
DOI: 10.3390/ijms19092803
|View full text |Cite
|
Sign up to set email alerts
|

Excellent Degradation Performance of a Versatile Phthalic Acid Esters-Degrading Bacterium and Catalytic Mechanism of Monoalkyl Phthalate Hydrolase

Abstract: Despites lots of characterized microorganisms that are capable of degrading phthalic acid esters (PAEs), there are few isolated strains with high activity towards PAEs under a broad range of environmental conditions. In this study, Gordonia sp. YC-JH1 had advantages over its counterparts in terms of di(2-ethylhexyl) phthalate (DEHP) degradation performance. It possessed an excellent degradation ability in the range of 20–50 °C, pH 5.0–12.0, or 0–8% NaCl with the optimal degradation condition 40 °C and pH 10.0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 51 publications
(74 reference statements)
0
18
0
Order By: Relevance
“…Interestingly, the esterase is capable of hydrolyzing both phthalate diesters and phthalate monoesters and is active over a wide range of temperature and pH without any cofactor requirement. Although phthalate hydrolases have long been isolated from cultured microbial sources and typically possess the catalytic serine within the consensus G-x-S-x-G motif [36][37][38]40], to the best of our knowledge, EstM2 is the first phthalate hydrolase, isolated from a soil metagenomic library that belongs to family VIII esterases possessing a β-lactamase like catalytic triad for phthalate ester hydrolysis. It is believed that structural modification of the enzyme by site-directed mutagenesis may further enhance the catalytic performance of EstM2 towards various estrogenic phthalates and may find use to counter the growing pollution caused by phthalate-based plasticizers in diverse geological environment and in other aspects of biotechnological applications.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the esterase is capable of hydrolyzing both phthalate diesters and phthalate monoesters and is active over a wide range of temperature and pH without any cofactor requirement. Although phthalate hydrolases have long been isolated from cultured microbial sources and typically possess the catalytic serine within the consensus G-x-S-x-G motif [36][37][38]40], to the best of our knowledge, EstM2 is the first phthalate hydrolase, isolated from a soil metagenomic library that belongs to family VIII esterases possessing a β-lactamase like catalytic triad for phthalate ester hydrolysis. It is believed that structural modification of the enzyme by site-directed mutagenesis may further enhance the catalytic performance of EstM2 towards various estrogenic phthalates and may find use to counter the growing pollution caused by phthalate-based plasticizers in diverse geological environment and in other aspects of biotechnological applications.…”
Section: Resultsmentioning
confidence: 99%
“…As far as metabolism of phthalate esters is concerned, there are only a few reports on the purified dialkyl phthalate esterase enzymes, which are capable of specifically hydrolyzing only one of the ester bonds of the diester to generate the corresponding monoalkyl phthalate esters [28,[30][31][32][33][34][35]. On the other hand, there are only limited reports of specific monoalkyl phthalate esterases that hydrolyze monoalkyl phthalates to furnish phthalic acid but are incapable of hydrolyzing phthalate diesters [5,[36][37][38][39][40]. Recently, another esterase isolated from naphthalene-enriched soil community, was shown to hydrolyze various polyaromatic esters besides dimethyl phthalate [41].…”
Section: Introductionmentioning
confidence: 99%
“…The amino acid sequences of alpha/beta hydrolases in the genome of Acidovorax sp. 210-6 and hydrolases derived from several aerobic o -phthalic acid-degrading Actinobacteria [1416, 67, 7577], Alphaproteobacteria (78, 79), Firmicutes [80], Gammaproteobacteria [81], and uncultured bacterium [82] were used for inferring maximum likelihood tree. The bacterial source, substrate specificity, and accession number of these aerobic hydrolases are listed in Table S1 .…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have reported aerobic microbial degradation pathways for different PAEs [3]. In the aerobic pathway, DEHP is initially transformed into ophthalic acid and 2-ethylhexanol through mono-(2-ethylhexyl) phthalate (MEHP) by dialkyl phthalate hydrolase and monoalkyl phthalate hydrolase [14][15][16][17] (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported aerobic microbial degradation pathways for different PAEs ( 4 ). In the aerobic pathway, DEHP is initially transformed into o -phthalic acid and 2-ethylhexanol through mono-(2-ethylhexyl) phthalate (MEHP) by dialkyl phthalate hydrolase and monoalkyl phthalate hydrolase ( 14 16 ) ( Fig. 1 ).…”
Section: Introductionmentioning
confidence: 99%